2010
DOI: 10.1108/13612021011025438
|View full text |Cite
|
Sign up to set email alerts
|

Tall women's satisfaction with the fit and style of tall women's clothing

Abstract: Purpose -The purpose of this paper is to assess tall women's satisfaction with the fit and style of apparel for tall women. Design/methodology/approach -A total of 75 US women, who were at least 5 feet 8 inches and between 18 and 54 years old, were asked to rate their level of satisfaction with misses-size and tall-size apparel, in general, and with seven garment categories (jackets/blazers/coats, button-up blouses, pullover tops/sweaters, skirts, jeans, pants, lingerie). Findings -T-tests revealed that partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…This study demonstrated that larger-size male consumers have more fit issues and are in need of better fitting jackets, and may be potential consumer group for mass customization, which coincides with a previous study. 37 Jones and Giddings 51 suggest mass customization as a solution for such consumers. The current study was limited in testing the production of mass customized jackets for plus-size men; the majority of the participants were in the normal and overweight BMI ranges, and only one participant was in the obese BMI range with large chest and waist circumferences.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that larger-size male consumers have more fit issues and are in need of better fitting jackets, and may be potential consumer group for mass customization, which coincides with a previous study. 37 Jones and Giddings 51 suggest mass customization as a solution for such consumers. The current study was limited in testing the production of mass customized jackets for plus-size men; the majority of the participants were in the normal and overweight BMI ranges, and only one participant was in the obese BMI range with large chest and waist circumferences.…”
Section: Resultsmentioning
confidence: 99%
“…Most clothing products are manufactured based on average height and weight of consumers, so those who do not have an average size experience dissatisfaction with clothing size (Shim & Kotsiopulos, 1990). Many studies on clothing size dissatisfaction of consumers who are not of average size focused on plus-size women (Chowdhary & Beale, 1988;Kim, 2006;Lee, 2011c;Shim & Kotsiopulos, 1990), and not many dealt with tall women (Jones & Giddings, 2010;Kersch, 1984;Lee, 1997a). Lee (1997b) said that tall women had the highest dissatisfaction about clothing size, and Jones and Giddings (2010) said tall women were dissatisfied about clothing size of misses-size clothes and had especially low satisfaction for pants.…”
Section: Clothing Size Satisfactionmentioning
confidence: 99%
“…Many studies on clothing size dissatisfaction of consumers who are not of average size focused on plus-size women (Chowdhary & Beale, 1988;Kim, 2006;Lee, 2011c;Shim & Kotsiopulos, 1990), and not many dealt with tall women (Jones & Giddings, 2010;Kersch, 1984;Lee, 1997a). Lee (1997b) said that tall women had the highest dissatisfaction about clothing size, and Jones and Giddings (2010) said tall women were dissatisfied about clothing size of misses-size clothes and had especially low satisfaction for pants. They claimed that while pants were purchased more from tall-size clothes, other categories were purchased more from misses-size clothes.…”
Section: Clothing Size Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles focused on the relations between physical features and apparel styles, including body shape, height, weight, facial features and skin colour et al (Jones and Giddings, 2010, Grogan et al, 2013, Park et al, 2009, Kim and Damhorst, 2010, Lee et al, 2007. Grogan et al (2013), found that people use clothes to increase body confidence, camouflage and try to attain a slender hourglass look.…”
Section: The Research Gap In User Profilesmentioning
confidence: 99%